Advancing Australia's Agenda for Young Children's Health and Wellbeing: Empirical Insights into Educator Knowledge, Confidence and Intentions in Promoting Children's Learning, Eating, Active Play and Sleep (LEAPS). Issue 2 (June 2018) - Cleland, Phoebe; Byrne, Rebecca; Vidgen, Helen; Irvine, Susan; Farrell, Ann; Gallegos, Danielle
EDUCATORS IN EARLY CHILDHOOD education and care (ECEC) settings play a critical role in advancing Australia's agenda for children's health and wellbeing. The LEAPS (Learning, Eating, Active Play, Sleep) professional development program was designed to acknowledge and improve educator knowledge of national healthy eating and physical activity guidelines, as a critical foundation for health and wellbeing of children and families. The program consisted of online reading and face-to-face professional development. Change in educator knowledge and confidence was assessed via pre- and post-questionnaire, with two additional open-ended questions regarding intention to change practice post-program. Educators (n = 765) participating in LEAPS increased their knowledge of nutrition and physical activity guidelines, and planned to implement practice changes as a result—namely communication of healthy eating and physical activity messages with colleagues, parents and children; and engaging parents in these areas within their service. Professional development regarding health guidelines is important to support evidence-based communication between educators and parents.